2006
DOI: 10.1111/j.1440-1843.2006.00951.x
|View full text |Cite
|
Sign up to set email alerts
|

Home respiratory muscle training in patients with chronic obstructive pulmonary disease

Abstract: This version is available at https://strathprints.strath.ac.uk/45007/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 20 publications
3
17
0
Order By: Relevance
“…Adherence to the intervention was good in our study and our group reached a mean pressure of 62% PImax (11.7) at the end of the programme, well above the 30% PImax minimal intensity required to achieve a training effect [27] and similar to other home IMT studies [51,52]. Our study suggests that a community-based programme, shorter than previously reported in research [24,25], could be effective in improving PImax and perception of well-being in community patients.…”
Section: Clinical Implications Limitations and Further Researchsupporting
confidence: 49%
See 3 more Smart Citations
“…Adherence to the intervention was good in our study and our group reached a mean pressure of 62% PImax (11.7) at the end of the programme, well above the 30% PImax minimal intensity required to achieve a training effect [27] and similar to other home IMT studies [51,52]. Our study suggests that a community-based programme, shorter than previously reported in research [24,25], could be effective in improving PImax and perception of well-being in community patients.…”
Section: Clinical Implications Limitations and Further Researchsupporting
confidence: 49%
“…Previous home-based IMT studies that have demonstrated increases in walking distance had longer durations of training [24,25,46], therefore it is possible that the duration of our IMT programme was a factor explaining this lack of improvement, although the duration of our programme was typical of UK practice. We did, however, find that the heart rate at the end of the ISWT in the PrBr-IMT group was slightly lower post-IMT than in the control group.…”
Section: Effects Of the Imt Programme On Respiratory Muscle Endurancementioning
confidence: 68%
See 2 more Smart Citations
“…As the pressure-generating capacity of the respiratory muscles falls and as the ratio of the pressures produced by the respiratory muscles to the maximum pressure that can be achieved increases dyspnea progressively worsens [11]. Since there is an established association between respiratory muscle dysfunction and dyspnea, an improvement in respiratory muscle function with inspiratory muscle training (IMT) could lead to a reduction in dyspnea [12,13]. A meta-analysis of IMT in 17 clinical trials found limited support for its use in terms of improving pulmonary function, respiratory muscle strength and endurance, exercise capacity, and functional status in patients with COPD [14][15][16].…”
Section: Introductionmentioning
confidence: 99%